Prevalence and Chemo-kinesis of Toxic Trace Metals in Environmental Samples - Hilia, I.; Hange, C.; Hakala, F.; Matheus, M.; Jansen, C.; Hidinwa, J.; Awofolu, O. (Namibian Journal for Research, Science and Technology, 2018)
The aim of the study was to assess incidences, level and mobility of some toxic trace metals in environmental samples. By this, the potential impacts of anthropogenic activities on environmental and human health would be evaluated. Soil, plant and lower animal samples were randomly collected from stratified study area, labelled and taken to the laboratory for pre-treatment and analysis. Acid digestion technique was employed for the isolation of metallic contents in samples and quantitation was by Inductively-Coupled Plasma Atomic Emission Spectroscopy (ICP-OES). The analytical protocol was validated through the quality assurance process which was found acceptable with quantitative metallic recoveries in the range of 85-90 %; hence considered applicable for the analyses of samples. The mean concentration of analysed metals in soil samples ranged from 53.2- 2532.8 mg/kg (Cu); 59.5- 2020.1 mg/kg (Zn); 1.80 – 21.26 mg/kg (Cd) and 19.6- 140.9 mg/kg (Pb). The mean level in grass samples ranged from 9.33 – 38.63 mg/kg (Cu); 64.20-105.18 mg/kg (Zn); 0.28–0.73 mg/kg (Cd) and 0.53 -16.26 mg/kg (Pb) while the mean level in lower animal sample (beetle) varied from 9.6 - 105.3 mg/kg (Cu); 134.1-297.2 mg/kg (Zn); 0.63 – 3.78 (Cd) and 8.0 – 29.1 mg/kg (Pb) across sample collection points (SCPs) 1-4 respectively. Metallic transfer factors (TFs) were in the order Zn >Cd > Cu> Pb with metal Pollution Indices (MPIs) in the order SCP1 > SCP2 > SCP3 > SCP4. About 60-70 % of analysed metals were above the Maximum Allowable Limits (MALs) in soil and plant samples using the European Economic Commission (EEC) and CODEX MALs respectively. Results obtained revealed general prevalence of analysed metals at all sampled sites with indication of metallic mobility across the food chain. This signifies dire consequences for environmental and human health. Control of pollution from source and passive environmental remediation strategies are recommended.